2007
DOI: 10.1083/jcb.200702101
|View full text |Cite
|
Sign up to set email alerts
|

A novel role in cytokinesis reveals a housekeeping function for the unfolded protein response

Abstract: The unfolded protein response (UPR) pathway helps cells cope with endoplasmic reticulum (ER) stress by activating genes that increase the ER's functional capabilities. We have identified a novel role for the UPR pathway in facilitating budding yeast cytokinesis. Although other cell cycle events are unaffected by conditions that disrupt ER function, cytokinesis is sensitive to these conditions. Moreover, efficient cytokinesis requires the UPR pathway even during unstressed growth conditions. UPR-deficient cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
58
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 60 publications
(64 citation statements)
references
References 65 publications
(95 reference statements)
5
58
1
Order By: Relevance
“…This is measured by the unfolded protein response (UPR), which is up-regulated when protein-folding capacity of the ER is compromised or otherwise overloaded (for review, see Hampton, 2000). We confirmed that the UPR is up-regulated greater than twofold when COD1/ SPF1 is deleted (Cronin et al, 2002) and when HOF1 is deleted (Bicknell et al, 2007), and we determined that cells lacking ERV25 also have a significantly up-regulated UPR (data not shown). The other HER mutants showed no elevation in UPR.…”
Section: M Federovitch Et Alsupporting
confidence: 62%
“…This is measured by the unfolded protein response (UPR), which is up-regulated when protein-folding capacity of the ER is compromised or otherwise overloaded (for review, see Hampton, 2000). We confirmed that the UPR is up-regulated greater than twofold when COD1/ SPF1 is deleted (Cronin et al, 2002) and when HOF1 is deleted (Bicknell et al, 2007), and we determined that cells lacking ERV25 also have a significantly up-regulated UPR (data not shown). The other HER mutants showed no elevation in UPR.…”
Section: M Federovitch Et Alsupporting
confidence: 62%
“…Under these conditions, ire-1 and xbp-1 deficiency reduces basic ER functions, including translation, folding, secretion and degradation of proteins passing through the secretory pathway. These findings may explain a wide range of physiological defects associated with UPR deficiencies (Bicknell et al, 2007;Fonseca et al, 2012;Henis-Korenblit et al, 2010;Hu et al, 2009;Lee et al, 2008;Reimold et al, 2000;Reimold et al, 2001;Richardson et al, 2010;Souid et al, 2007;Todd et al, 2008;Zhao et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…A functional UPR is also required for the development of hepatic, bone marrow and B cells, as well as for yeast cytokinesis (Bicknell et al, 2007;Hu et al, 2009;Lee et al, 2008;Reimold et al, 2001;Todd et al, 2008). In C. elegans, ire-1/xbp-1-depleted animals are hypersensitive to ER stress (Shen et al, 2001) and pathogens (Richardson et al, 2010) and have a shortened lifespan (Henis-Korenblit et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to plasma cell differentiation, where facilitating ER expansion to accommodate massive antibody secretion provides a satisfying conceptual reason for UPR activation, reasons for IRE1 activation in earlier stages of B-cell development or during T-cell development are not immediately obvious. In this regard, it is interesting to note our recent findings describing a role for IRE1 in cytokinesis in the budding yeast Saccharomyces cerevisiae (35). As for early B or T cells, cytokinesis is not associated with a global increase in protein secretion or membrane protein expression, although localization of a specific cell cycle component(s) to the site of cytokinesis may require some increase in secretory capacity.…”
Section: Cd8mentioning
confidence: 99%